PENGARUH GOOD CORPORATE GOVERNANCE DAN COMPANY SIZE TERHADAP INCOME SMOOTHING DENGAN PROFITABILITAS SEBAGAI VARIABEL PADA PERUSAHAAN LQ 45 YANGTERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Firman Syarif; Anggriyani Anggriyani (Universitas Negeri Medan (UNIMED), 2017)
This research examines the impact given by Good Corporate Governace (proxied by Managerial Ownership and The Board Of Commisioners) and Board Size that either simultaneously and partially affectEarnings Management and Profitability (proxied by Return On Assets) as moderating variabel that effect relationship Good Corporate Governance (proxied by Managerial Ownership and The Board Of Commisioners) and Board Size that either Earnings Management of company listed on LQ 45 in Indonesian Stock Exchange in 2012-2014. Population of this research was 45 company listed on LQ 45 from 2012 to 2014. And research sample was selected using purposive sampling method resulting 21 company chosen over 45 company as the research sampling. Data was processed by coefficient of determination test, F test, and t tes for the first hypothesis while the second hypothesis testing for moderating variabel using residual test. The result of this research showed thatManagerial Ownership, The Board of Commisioners, and Board size affect Earnings Management are not simultaneously influence and partially.Result for Profitability (proxied by Return On Assets) be able to moderate the relationship beetween Good Corporate Governace (proxied by Managerial Ownership and The Board Of Commisioners) and Board Size to Earnigngs Management of Company list on LQ 45 in Indonesian Stock Exchane in 2012-2014. Keywords : Good Corporate Governace, Managerial Ownership, The Board Of Commisioners, Board Size, Profitability, Return On Asset, LQ 45 index.